Field Evaluation of Zero Inertia and Kinematic Wave Models under Furrow Irrigated Bed System in Vertisols - Gautam, K M; Kumar, Virendra; Purohit, R C (Journal of Agricultural Engineering, 2008)
In this field study zero inertia and kinematic wave models have been applied to predict advance and recession times under furrow irrigated bed system. SRFR Version 4.06 software of surface irrigation has been used to obtain the numerical solution of Saint-Venant equation. The predicted advance and recession times were compared with the observed ones. Slope of best fit line, coefficient of determination and standard error indices were calculated and used to evaluate the performance of the models. Zero inertia and Kinematic wave model under estimated (?&lt1) the advance and recession time in furrow irrigated bed system. The Zero inertia model predicted comparatively more reliable result in predicting advance and recession time for the field conditions encountered in the study. Both the models, zero inertia and kinematic wave, however predicted advance and recession times slightly more accurately in stream size 2 Ips than 1 Ips per furrow.